A web based intelligent tutoring system for arithmetic / Tharanitharan Kuppusamy - Tharanitharan , Kuppusamy (2001)
The 21st century among others has depicted a wide array of events and technologies in its quest to revolutionize all aspects of life in a multitude dimension of fields. The field of learning which is among the oldest field of human achievement is one of the most important fields that constantly need new techniques and methods to help students to achieve better. The days of a student sitting through books and other paper works is slowly disappearing to give way to the new medium such as the computer and internet. Slowly, but surely. Today, many educational packages are on the market and the internet for a long time. These packages cater for a variety of people which include students, teachers and even parents. Many are good but some do have its short comings. Keeping this in mind, I decided to build an intelligent tutoring system for arithmetic. The syllabus of arithmetic is designed such as to mould the students who are thought the very basics in primary school to further enhance their capabilities in mathematics. They are though a higher level of mathematics more effectively to help prepare them further higher level of mathematics that will be thought in upper secondary school. I believe it’s important to build a strong foundation and liking for mathematics in order to ensure that they will be ready to face new and often exciting challenges that they will encounter in their studies. To love something, we have to like something. And to like something, we have to know something. That is the primary aim in this quest to develop a system that will not only help tremendously the students but also create an awareness and liking for mathematics. The intelligent tutoring system is thus proposed to overcome any shortcoming that other systems in other fields have. To start with, the ITS is a web-based learning system. It covers all the syllabus that will be tested in UPSR. The system provides short notes, quiz, interesting bits of mathematics and its history and a modal examination paper to prepare students for the examination. The proposed system will have an attractive users interface which includes images be it graphic or animation to make the learning process more fun and efficient. And to help lost or inexperienced computer users the system will be built to cater the needs and help students along the way. In order to build a comprehensive system, related information is gathered from the books, internet and other learning material. Internet is chosen to be the platform for the development of this project. Interested users will find it easy to access this system at any time and will be free to go through, evaluate and to use it since it’s on the web and freely available. This system will be built using a number of programming tools like HTML, JavaScript and C. to make it more interesting, other graphic tools like Flash and Dreamweaver to further develop this system. It is hoped that the development of this ITS will further assist students to better appreciate and develop a liking towards mathematics and ultimately achieve better skills in mathematics.